Pemancar Jaringan Internet Off-Grid Solar System berbasis IoT guna Meningkatkan Promosi Pariwisata dan Ekonomi Kreatif Pantai Nanggelan - Sya'Bana, Ahmad Archam; Khoiri, Ahmad Hipnie; Ramadhan, Fila; Suseno, Nadia Hidayanti; Zaghasy, Daffa Athala; Rachmanita, Risse Entikaria (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2024)
The internet is a primary need for humans in the modern era today. The internet can be utilized for various fields, one of which is the economic field. This is in line with the innovation of the Internet Network in Blankspot Areas Using a 100 Watt Peak Photovoltaic System-Based Cellular Base Transceiver Station (BTS) for the Promotion of Nanggelan Beach Tourism, Jember. This design is a system design for utilizing the internet network using off-grid electrical energy in Jawala Village. The purpose of this community service is to assist the community in the economic field by utilizing Nanggelan Beach as the main object of promotion. The implementation methods in this service include socialization and creation of an Instagram account; tool fabrication, application, implementation, and tool handover; assistance and monitoring; training on tool usage and maintenance; creation of a partner guidebook; handover of the partner guidebook; completion of program outputs, and evaluation will be given in the form of a Google Form link as a suggestion box for evaluation. As for the result of this community service, the people of Jawala Village can promote Nanggelan Beach using Instagram. Tourists who will visit Nanggelan Beach will experience the internet from the results of this community service program.